2023
DOI: 10.3390/su15129586
|View full text |Cite
|
Sign up to set email alerts
|

An Overview and Countermeasure of Global Wave Energy Classification

Abstract: Wave energy will be an important support to deal with the energy crisis of human society. A scientific energy classification scheme is a prerequisite support for the macro-scale optimized layout, micro-scale accurate site selection and a blueprinting of development routes for wave energy. Based on the indicator considered, this study first divides the global wave energy classification into three stages: preliminary exploration stage, mid-term development stage and relatively mature stage, and then sorts out th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The highest wind power density sites are located in Ardabil, Gorgan, and Zanjan. Zheng et al [17] identified six common bottlenecks in current energy classification schemes, including inconsistencies with physical mechanisms, inability to meet diverse task requirements, and applicability issues in certain seasons/months. To address these challenges, a dynamic adaptive wave energy classification scheme that takes into account various factors is adaptable for different tasks, is available at any time, and is suitable for use across regions has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The highest wind power density sites are located in Ardabil, Gorgan, and Zanjan. Zheng et al [17] identified six common bottlenecks in current energy classification schemes, including inconsistencies with physical mechanisms, inability to meet diverse task requirements, and applicability issues in certain seasons/months. To address these challenges, a dynamic adaptive wave energy classification scheme that takes into account various factors is adaptable for different tasks, is available at any time, and is suitable for use across regions has been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Within this field, wave energy has some important advantages, especially due to the continuous availability of the source, all day and year-round, and to its low environmental impact compared to other energy sources, since it does not generate emissions or pollution during its operation [2]. However, there are also challenges to consider, such as the technical complexity of designing and maintaining wave energy conversion systems, the high initial costs of implementing these technologies, and significant seasonal variability in wave energy [3,4].…”
Section: Introductionmentioning
confidence: 99%